2019
DOI: 10.1093/wber/lhy024
|View full text |Cite
|
Sign up to set email alerts
|

Be Wary of Those Who Ask: A Randomized Experiment on the Size and Determinants of the Enumerator Effect

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…These temporal features enable us to capture additional contexts of the interview. For instance, as noted by Di Maio and Fiala (2020), controlling for interviewer fixed effects can help address interviewer fatigue which could interact with response fatigue in ways that can affect the estimates on the outcome of interest.…”
Section: Summary Statistics and Descriptive Resultsmentioning
confidence: 99%
“…These temporal features enable us to capture additional contexts of the interview. For instance, as noted by Di Maio and Fiala (2020), controlling for interviewer fixed effects can help address interviewer fatigue which could interact with response fatigue in ways that can affect the estimates on the outcome of interest.…”
Section: Summary Statistics and Descriptive Resultsmentioning
confidence: 99%
“…Recent research on interviewer effects in a randomized experiment in Uganda by Di Maio and Fiala (2019) found that interviewer characteristics and their differences from respondent characteristics affected survey responses and ultimately data quality for sensitive topics. On the contrary, responses to less sensitive topics were much less, or not at all, susceptible to interviewer characteristics.…”
Section: Interviewer Effectsmentioning
confidence: 99%
“…Past stud ies of in ter viewer ef fects have been able to ex ploit the ex og e nous as sign ment of in ter view ers to re spon dents but have been lim ited by the fact that the in ter viewer char ac ter is tics in ques tion are both fxed and cor re lated with other at tri butes. For ex am ple, race is cor re lated with in come and so cio eco nomic sta tus, and a wide range of in ter viewer char ac ter is tics can all af fect re sponses si mul ta neously (Di Maio and Fiala 2019). Because in ter view ers in our study were ex og e nously shocked with new in for ma tion about HIV trans mis sion rates, we can iso late the causal ef fect of knowl 3 You Know What I Know edge alone.…”
Section: Introductionmentioning
confidence: 99%